Bangla Desh economy: problems and prospects - Rao, V. K. R. V. (Delhi : Vikas Publications, 1972)
This book enlighten the general reader on the economic background underlying the Bangla Desh struggle for national liberation.
Includes bibliographical references.
hza 29/01/2019
Loans
Keywords: Economics; Bangladesh